Study of Salmonella typhimurium mutagenicity assay of (E)-piplartine by the Ames test - Morandim-Giannetti, Andreia de A.; Cotinguiba, Fernando; Regasini, Luis O.; Frigieri, Mariana C. [UNESP]; Varanda, Eliana Aparecida [UNESP]; Coqueiro, Aline; Kato, Massuo J.; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP] (Academic Journals, 2011)
Phytochemical studies carried out with Piperaceae species have shown great diversity of secondary metabolites among which are several displayed considerable biological activities. The species Piper tuberculatum has been intensively investigated and a series of amides have been described. For instance, (E)-piplartine showed significant cytotoxic activity against tumor cell lines, especially human leukemia cell lines; antifungal activity against Cladosporium species; trypanocidal activity and others. Considering the popular use of P. tuberculatum and the lack of pharmacological studies regarding this plant species, the mutagenic and antimutagenic effect of (E)-piplartine was evaluated by the Ames test, using the strains TA97a, TA98, TA100 and TA102 of Salmonella typhimurium. No mutagenic activity was observed for this compound.
Keywords: Piperaceae; Piper tuberculatum; (Z)-piplartine; mutagenic activated; Ames test